2022
DOI: 10.1038/s41380-021-01422-5
|View full text |Cite
|
Sign up to set email alerts
|

Altered canonical and striatal-frontal resting state functional connectivity in children with pathogenic variants in the Ras/mitogen-activated protein kinase pathway

Abstract: Mounting evidence supports the role of the Ras/mitogen-activated protein kinase (Ras/MAPK) pathway in neurodevelopmental disorders. Here, the authors used a genetics-first approach to examine how Ras/MAPK pathogenic variants affect the functional organization of the brain and cognitive phenotypes including weaknesses in attention and inhibition. Functional MRI was used to examine resting state functional connectivity (RSFC) in association with Ras/MAPK pathogenic variants in children with Noonan syndrome (NS).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 71 publications
(97 reference statements)
0
4
0
Order By: Relevance
“…Interestingly, deficits in emotion regulation processing in children with idiopathic ADHD have been linked to altered development of the striato‐amygdalo‐medial prefrontal cortical network, 40 which is known to be impacted in children with Noonan syndrome and PTPN11 pathogenic variants 17 . Children with Noonan syndrome also demonstrate hyperconnectivity within striatal‐frontal networks in comparison with typically developing children, 15 indicating that children with Noonan syndrome may be at increased risk for dysfunction within these pathways that contribute to difficulties with emotion regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, deficits in emotion regulation processing in children with idiopathic ADHD have been linked to altered development of the striato‐amygdalo‐medial prefrontal cortical network, 40 which is known to be impacted in children with Noonan syndrome and PTPN11 pathogenic variants 17 . Children with Noonan syndrome also demonstrate hyperconnectivity within striatal‐frontal networks in comparison with typically developing children, 15 indicating that children with Noonan syndrome may be at increased risk for dysfunction within these pathways that contribute to difficulties with emotion regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Informed consent was provided by the parent or guardian of all participants, with assent given by participants over age 7 years, as approved by the institutional review board of Stanford University (IRB #3192). A subset of the 45 children with Noonan syndrome described in the present paper were also included in previous work from our group ( n = 39 in Bruno et al, 15 n = 17 in Fattah et al, 16 n = 12 in Johnson et al 17 ). Detailed recruitment and exclusion criteria are presented in Appendix S1.…”
Section: Methodsmentioning
confidence: 99%
“…Gene discovery has also demonstrated that the encoded proteins of varied genes involved with ASD and other neuropsychiatric disorder cluster within the Ras/MAPK signaling pathway suggesting that these disorders are associated with enrichment of Ras/MAPK signaling [21,22]. Finally, NS significantly impacts brain development resulting in altered brain structure [23][24][25] and functional connectivity [26].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, NS has a large effect on neurobiological development [23,24,26], which may represent an important intermediate phenotype (i.e. endophenotype) between Ras/MAPK pathogenic variants and neuropsychiatric phenotypes (Fig 1b .).…”
Section: Introductionmentioning
confidence: 99%